2020
DOI: 10.1186/s43014-019-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound power on extraction kinetic model, and physicochemical and structural characteristics of collagen from chicken lung

Abstract: The effects of ultrasound power on extraction kinetic model, and physicochemical and structural characteristics of collagen from chicken lung were studied. Ultrasound power caused a significant increase in extraction rate and equilibrium concentration, with the maximum extraction yield (31.25%) at 150 W. The experimental data were consistent with the predicted ones in this empirical equation, in which the percentage error differences was 0.026-4.159%. Besides, ultrasound treatment did not affect their triplehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Ultrasounds induce cavitation in the liquid solvent, forming microbubbles whose collapse damages the fish tissues and increases the contact area between liquid and solid with a range of wave 20 to 1000 kHz. Shear forces produced by cavitation bubbles relate with their size so that with an increase in the ultrasonic frequency, the size of the bubbles decreases, and the shear forces increase [ 105 , 106 , 107 , 108 ]. Zou et al [ 105 ] reported that the yield of the collagen extracted from soft-shelled turtle calipash increased by 16.3% when using ultrasound pretreatment (24 min, 200 W, and 24 kHz sonication) compared to the yields measured in conventional AcOH extractions.…”
Section: Other Extraction Methodsmentioning
confidence: 99%
“…Ultrasounds induce cavitation in the liquid solvent, forming microbubbles whose collapse damages the fish tissues and increases the contact area between liquid and solid with a range of wave 20 to 1000 kHz. Shear forces produced by cavitation bubbles relate with their size so that with an increase in the ultrasonic frequency, the size of the bubbles decreases, and the shear forces increase [ 105 , 106 , 107 , 108 ]. Zou et al [ 105 ] reported that the yield of the collagen extracted from soft-shelled turtle calipash increased by 16.3% when using ultrasound pretreatment (24 min, 200 W, and 24 kHz sonication) compared to the yields measured in conventional AcOH extractions.…”
Section: Other Extraction Methodsmentioning
confidence: 99%
“…Petcharat et al demonstrated that ultrasonication at an 80% amplitude for 10 min increased collagen yield from clown featherback fish without affecting collagen’s molecular structure. Furthermore, case studies by Zou et al [ 87 ] and Akram and Zhang [ 88 ] compared the extraction of chicken collagen with and without ultrasonication, as well as with and without pepsin and discovered that ultrasound power significantly increased the extraction rate and equilibrium concentration. Both studies reported that FTIR results showed intact collagen triple helical structures.…”
Section: Extraction Of Collagen Type Imentioning
confidence: 99%
“…24,28,30,41,57,104,105 In addition, structural and morphological properties of collagen are also of interest. 19,26,51 Previous works have shown that modification of extraction parameters may alter the properties of collagen to a certain extent.…”
Section: Recovery By Ultrafiltration (Uf)mentioning
confidence: 99%
“…In recent efforts to eliminate the use of chemicals during raw material pre‐treatment before collagen extraction, one study has successfully removed non‐collagenous components by fermenting fish skin with Bacillus velezensis FEL‐BM21 25 . Combining integrated approaches during the extraction step, such as ultrasound‐assisted extraction, 26‐28 microwave‐assisted extraction, 29 and physical‐aided extraction, 30,1 has increased process efficiency by aiding the opening of collagen fibrils during acid and enzymatic treatment, resulting in a considerably reduced extraction time. Furthermore, ultrafiltration to retrieve collagen post‐extraction has improved the tedious and time‐consuming salt precipitation and dialysis process of collagen recovery 32,33 .…”
Section: Introductionmentioning
confidence: 99%